Study of Genetic Variations in Detoxification Genes GSTT1 and GSTM1 in Thalassemia Patients in Dhi Qar Province - Noor Yousif Jabeer; Hassan Risan Al-Rikabi (International Journal of Medical Toxicology and Legal Medicine, 2024)
Thalassemia is the most well-known hereditary blood disorder that causes this symptom Anemia is caused by defective genes, after which you feel the absence of globin proteins in the body. Thalassemia results from genetic defects that hinder the normal production of hemoglobin. Hemoglobin is the basic protein found in red blood cells and is responsible for binding and carrying red blood cells for oxygen to be transported. From the lungs to various tissues of the body, normal hemoglobin in adults consists of two pairs of chains. One pair of chains is called and the other pair is called. The synthesis of these proteins must be coordinated to ensure equal levels in red blood cells. GSTs (GSTT1, GSTM1) genes are known detoxification factors. Genetic variation in these genes leads to the absence of functional activity of the enzyme or to a decrease or increase in metabolic activity. The aim of this study is to determine the effect of the absence of the detoxification genes GSTT1 and GSTM1 on the incidence of thalassemia in Dhi Qar Governorate. The total blood samples were 150 samples. 100 samples were from those with thalassemia, as they were collected from the Dhi Qar Center for Hereditary Blood Diseases, and 50 samples were from healthy people for the purpose of comparison, collected from various places. From the governorate, 1 ml of blood was used for the purpose of extracting DNA and then amplifying it with a multiplex PCR device and detecting genes using ultraviolet rays. As for the remaining blood, it was used for the purpose of conducting comprehensive blood tests.